Strategi Peningkatan Pemberdayaan Masyarakat melalui Pengembangan Potensi Desa Wisata di Kecamatan Gerung Kecamatan Lombok Barat - Ridwan Sya'rani (Yayasan Literasi Sains Indonesia, 2024)
West Lombok Regency West Nusa Tenggara Province is a regency famous for tourism. Economic growth in West Lombok Regency was slumped due to Covid 19. It is necessary to handle the community's economy to recover, including through the development of village -based tourism in Gerung District. The aim of the study was to determine the best strategy to increase community empowerment through the development of the potential of tourism villages in Gerung District, West Lombok Regency, West Nusa Tenggara Province. The results of the SWOT analysis and diagram of the strategic factors determining the increase in community empowerment through the development of the potential of tourism villages in Gerung sub-district showed that the best strategy included in the quadrant I. The quadrant shows that the strategy utilizes existing strengths and opportunities. Alternative strategies based on SWOT formulations that can be implemented are: (1) Optimizing village potential and tourist visits for tourism development (2) optimizing sub -district support and potential tourist visits for community empowerment (3) Utilizing tourism awareness groups for village tourism development and (4) Optimizing the support of the sub -district head for tourism awareness groups. The implementation of this SWOT formulation is intended for policy considerations in the preparation of the sub-district strategic plan in the field of community empowerment. Suggestions for the results of this SWOT study are that the sub -district and district governments involve the community in developing the potential of tourism villages in Gerung District based on the strategies that have been set.